Study of bolts used as shear connectors in concrete-filled steel tubes. (15th March 2021) - Chaves, Marina de Fátima Ferreira; Xavier, Ellen Martins; Sarmanho, Arlene Maria Cunha; Ribeiro Neto, Juliano Geral
Highlights: This study investigates the resistance capacity per bolt used as a shear connector in concrete filled steel tube columns using numerical models. The numerical model was developed and calibrated with the experimental test. The different bolt lengths and concrete strengths and did not exhibit a raise in the load capacity in the models. The steel tube thickness study shown that should be a relation between the diameter of the bolt and the thickness of the steel tube between 1.3 e 2.0. Abstract: This research presents a numerical analysis of bolts used as mechanical connectors in circular concrete-filled steel tube columns. The numerical model was calibrated with the experimental results and was analyzed different parameters such as bolt lengths, steel tube thickness, and concrete strength. The finite element model was developed in Abaqus software, using different constitutive models of concrete behavior. The results indicated that: (1) The thickness of the steel tube must be compatible with the diameter of the shear connector showing an ideal ratio between 1.3 and 2.0; (2) The length of the shear connector did not cause a significant change in the load capacity; (3) The minimum distance between the shear connectors of six times the diameter was enough to prevent overlap in their failure modes.